IMPORTANCE OF THE TERMINOLOGICAL USE OF ENGLISH IN INFORMATION COMMUNICATION TECHNOLOGIES - Yuldasheva , Fazilatxon (Educational Research in Universal Sciences, 2023)
The problem of studying the borrowings of ICT terms into our language, especially modern ICT terms has an international impact. English plays a great role in the assimilation of international ICT terms into many languages, including our language. It plays a huge role in the dissemination of international terms, as the main intermediary language. Based on etymology, lexical material from international borrowings and the rapid development of information technologies, make possible to study and analyze the importance of the terminological potential of the English language in the field of ICT and emphasizes the importance of studying modern trends in the emergence and implementation of new ICT terms in the scientific-technical field and the information space.